Additive Manufacturing as A New Technique of Fabrication - Dehghanghadikolaei, Amir (Journal of 3D Printing and Applications, 2018)
Additive manufacturing (AM) is reshaping fabrication in engineering and clinical settings. This editorial highlights metal AM routes—SLS, SLM, DMLS, and EBM—and their application to patient-specific NiTi implants, where biocompatibility and shape-memory behavior are compelling. We note the current gaps that matter in practice: process parameter tuning, post-processing (heat treatment, coating, machining/finishing), and their effects on mechanical performance and corrosion. We invite contributions that quantify these trade-offs and expand AM beyond metals into polymers and ceramics, with clear comparisons across processes and materials. Our goal is to surface actionable findings that improve part quality, reliability, and clinical/industrial readiness.
Keywords: Additive Manufacturing; Biocompatibility; Corrosion; Post-Processing; Heat Treatment